Prehistoric extinction of birds on Mangaia, Cook Islands, Polynesia. - Steadman, D W (1990)
Mangaia (Cook Islands) consists of a weathered volcanic interior encircled by limestones known as the makatea. Excavations at Tangatatau Rockshelter (site MAN-44), located on the inner cliff of the makatea, produced a stratified sequence of Polynesian artifacts and faunal remains ranging from A.D. 1000-1100 to A.D. 1500-1600. Resident species of birds represented at MAN-44 include nine seabirds (at least three extirpated on Mangaia) and 12 land birds (eight extirpated or extinct). Seven of the extinct/extirpated land birds are confined to the site's four lowest stratigraphic zones, which represent the first 200-300 yr of human occupation at MAN-44. During this time, human exploitation of vertebrates switched from primarily native land birds to almost exclusively small reef fish, domesticates (chickens, pigs), and commensals (rats). Sediment cores from a lake 0.9 km from MAN-44 show clear palynological and stratigraphic signals of human presence on Mangaia, especially forest clearance of the volcanic interior, beginning at 1600 yr B.P. The rugged makatea must have provided a forest refuge for birds during the first 700 yr of human presence, after which Mangaians exploited the previously little used makatea because forest resources (trees, other plants, birds) had been depleted on the now badly eroded volcanic interior. MAN-44 is the oldest archaeological site known on Mangaia. Whether other species of birds were lost in the period of human activity that preceded occupation of MAN-44 remains to be seen.